EFEKTIFITAS MIKROORGANISME LOKAL (MOL) LIMBAH BUAH-BUAHAN SEBAGAI AKTIFATOR PEMBUATAN KOMPOS - Ali, Haidina (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Constraints or public complaints in the process of composting organic wastelies in the composting process that takes a long time between 2-3 months and acceptanceof people who are less fit to existing activator as EM4 scarce in Rural. The purpose of thisstudy was to determine the effectiveness of the Local Microorganisms activator (MOL)waste fruits of the length of time the formation of compost organic waste. This type ofresearch is an experimental design using